2013
DOI: 10.1007/s00247-012-2589-6
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal ultrasonography of the lower extremities in infants and children

Abstract: Ultrasonography is a powerful diagnostic imaging tool for evaluating lower extremity anatomy and pathology in children. Indications for pediatric musculoskeletal lower extremity sonography include developmental dysplasia of the hip, hip joint sonography for the child with a painful hip, evaluation and characterization of superficial soft-tissue masses, evaluation for deep venous thrombosis, and foreign body localization, characterization and removal. This review highlights these established indications, but pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…US does not have these limitations; it is a readily available and inexpensive method with no radiation risk. Several studies have demonstrated that US, when performed by trained and experienced operators, is an effective tool for detecting occult ankle fractures and associated soft tissue injuries in children ( Gleeson et al 1996 , Farley et al 2001 , Callahan 2013 ). In our review, we observed a good diagnostic accuracy of US for diagnosing occult ankle fractures ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…US does not have these limitations; it is a readily available and inexpensive method with no radiation risk. Several studies have demonstrated that US, when performed by trained and experienced operators, is an effective tool for detecting occult ankle fractures and associated soft tissue injuries in children ( Gleeson et al 1996 , Farley et al 2001 , Callahan 2013 ). In our review, we observed a good diagnostic accuracy of US for diagnosing occult ankle fractures ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…US is widely used in the diagnosis of hip disorders in children [2]. In developmental displasia, it is essential for establishing an early diagnosis in order to allow a prompt treatment.…”
mentioning
confidence: 99%